Concordance of PD‐1 and PD‐L1 (B7‐H1) in paired primary and metastatic clear cell renal cell carcinoma. (12th December 2019) - Eckel‐Passow, Jeanette E.; Ho, Thai H.; Serie, Daniel J.; Cheville, John C.; Houston Thompson, R.; Costello, Brian A.; Dong, Haidong; Kwon, Eugene D.; Leibovich, Bradley C.; Parker, Alexander S.
Abstract: Objectives: Previous studies noted discordance of programmed death‐1 (PD‐1) and one of its ligands (PD‐L1) across patient‐matched primary and metastatic clear cell renal cell carcinoma (ccRCC). There are inconsistencies if the primary or metastatic tumor has higher expression, and whether metastatic tumor expression is associated with patient outcome. Thus, we examined PD‐1 and PD‐L1 in patient‐matched tumors using a large number of ccRCC patients with long follow‐up. Materials and Methods: We analyzed PD‐1 and PD‐L1 using immunohistochemistry in patient‐matched primary and metastatic tumors from 110 ccRCC patients. Concordance was assessed among longitudinal metastatic tumors, as well as across patient‐matched primary and metastatic tumors. Cox proportional hazards regression was used to evaluate the associations of metastatic tumor expression with cancer‐specific survival. Results: We observed inter‐metastatic tumor heterogeneity of PD‐1 in 25 (69%) of the 36 patients and of PD‐L1 in seven (19%) patients. Concordance between patient‐matched primary and metastatic tumors was 73% (Kappa = 0.16, 95% CI: −0.003‐0.32). Similarly, concordance of PD‐L1 between metastatic and patient‐matched primary tumors was 78% (Kappa = 0.27, 95% CI: 0.09‐0.46). Both markers demonstrated higher expression in primary vs metastatic tumors. Metastatic tumor expression of PD‐1 was significantly associated with metastatic location ( P  < .0001) and ccRCC‐specific survival (HR = 2.15, 95% CI: 1.06‐4.36, P  = .035). Conclusions: The expression of PD‐1 and PD‐L1 is discordant across patient‐matched ccRCC tumors, with higher expression in primary tumors. Higher PD‐1 expression was associated with metastatic location and lower cancer‐specific survival. If validated, these results highlight the importance of evaluating these biomarkers in metastatic tissue specifically. Abstract : We examined PD‐1 and PD‐L1 in patient‐matched tumors in a large cohort of ccRCC with long‐term follow‐up. The expression of PD‐1 and PD‐L1 was discordant across patient‐matched ccRCC tumors, with higher expression in primary tumors. Higher PD‐1 expression was associated with metastatic location and lower cancer‐specific survival.